Analisis Model Bisnis Usahatani Benih Kentang, Pakcoy, dan Stroberi (Studi Kasus di CV. Bumi Agrotech) - Putra, Harry Wiyono; Sadeli, Agriani Hermita; Indrawibawa, Diky (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Potatoes represent one of the alternative carbohydrate sources replacing rice and possess high economic value. According to the Central Bureau of Statistics (BPS) in 2023, Indonesia's potato production increased by 4.21 percent from 1.36 million tons to 1.42 million tons. CV. Bumi Agro Technology (CV. BAT) is one of the potato seed producers that diversify to minimize risks and ensure smooth cash flow. Potatoes, as their flagship commodity, have the highest sales. Strawberry seedlings serve as a substitute commodity if potatoes incur losses, while leafy vegetables ensure quick cash flow availability. To understand its business model, it is necessary to map CV. BAT's business model as a company that cultivates various commodities for diversification. The aim of this research is to map CV. BAT's business model. This research employs a qualitative design with a case study approach at CV. BAT. Data were obtained through observation and interviews. This study uses the analysis of nine blocks of the Business Model Canvas (BMC). The research findings conclude that CV. BAT indirectly fulfills the nine BMC blocks. CV. BAT heavily relies on the quality of its products to maintain consumer loyalty. Good product quality triggers repeat orders and consumer trust. Therefore, CV. BAT needs to maintain the quality of its products, especially potato and strawberry seed products.